The Usefulness of Perfusion Index Derived from a Pulse Oximeter in Predicting Hypotension following Spinal Anesthesia for Cesarean Section (Nepal Medical College Journal, 2022)
Hypotension is a frequent complication of spinal anesthesia. Decrease in peripheral vascular tone that occurs during pregnancy is one of the factors causing hypotension in patients undergoing cesarean section under spinal anesthesia. Perfusion index derived from pulse oximeter can be an easy and non-invasive measure of peripheral perfusion. This study was conducted to test the usefulness of pulse oximeter in predicting hypotension following spinal anesthesia for cesarean section. In this study, 247 parturients undergoing elective cesarean section under spinal anesthesia were included. Parturients who had baseline PI3.5 were kept in Group II. All the patients were given 0.5% bupivacaine heavy 2.2 ml for spinal anesthesia. In group I, 30 patients (23.62%) had hypotension whereas in Group II, 119 patients (100%) had hypotension. The episodes of hypotension were significantly lower in Group I as compared to Group II (p